Extracellular matrix stiffness regulates colorectal cancer progression via HSF4 - Kangtao Wang; Siyi Ning; Shuai Zhang; Mingming Jiang; Yan Huang; Haiping Pei; Ming Li; Fengbo Tan (Journal of Experimental & Clinical Cancer Research)
Abstract Background Colorectal cancer (CRC) has high incidence and mortality rates, with severe prognoses during invasion and metastasis stages. Despite advancements in diagnostic and therapeutic technologies, the impact of the tumour microenvironment, particularly extracellular matrix (ECM) stiffness, on CRC progression and metastasis is not fully understood. Methods This study included 107 CRC patients. Tumour stiffness was assessed using magnetic resonance elastography (MRE), and collagen ratio was analysed with Masson staining. CRC cell lines were cultured on matrices of varying stiffness, followed by transcriptome sequencing to identify stiffness-related genes. An HSF4 knockout CRC cell model was cultured in different ECM stiffness to evaluate the effects of HSF4 on cell proliferation, migration, and invasion in vitro and in vivo. Results CRC tumour stiffness was significantly higher than normal tissue and positively correlated with collagen content and TNM staging. High-stiffness matrices significantly regulated cell functions and signalling pathways. High HSF4 (heat shock transcriptional factor 4) expression was strongly associated with tumour stiffness and poor prognosis. HSF4 expression increased with higher TNM stages, and its knockout significantly inhibited cell proliferation, migration, and invasion, especially on high-stiffness matrices. In vivo experiments confirmed that HSF4 promoted tumour growth and metastasis, independent of collagen protein increase. Conclusions This study reveals that tumour stiffness promotes the proliferation and metastasis of CRC by regulating EMT-related signalling pathways through HSF4. Tumour stiffness and HSF4 could be valuable targets for prognostic assessment and therapeutic intervention in CRC.